The role and impact of information technology towards the Unemployment rate of human resource management - Munita, Tan (2015)
Information technology or IT is the term encompasses all form of technology which is used to create, store, retrieve, transmit, exchange and use up the information in various type of methods. IT has become and a very important and the basic to ensure and support the business processes in organizations. On the other hand, the presence of information technology indicates that the organizational change is skill-biased. Therefore, it is important for us to analyze the effect of organization and technological change to determine the process that will associate with changes. Hence, there are two objectives in this research that aims to be achieved. There are to determine the role of information technology in the human resource and to analyze the impact of information technology on the unemployment rate in the human resource management. The respondents of this research are the SME ICT companies in Penang, Malaysia. The research data are collected from the 46 respondents by email and phone call. The overall analysis was done by using SPSS. For achieving the first objective, mean test was used whereas Pearson Correlation was used to achieve the second objective. The results showed the rank of the role of information technology which communication was the first, followed by management information system, inventory management, customer relationship management and data management. In conclusion, the findings of this research also showed that there is strong positive and significant relationship between the role and impact of information technology towards the unemployment rate of the human resource management.